2023
DOI: 10.3390/ma16103875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steel Slag Powder Content and Curing Condition on the Performance of Alkali-Activated Materials Based UHPC Matrix

Abstract: The accumulation of steel slag and other industrial solid wastes has caused serious environmental pollution and resource waste, and the resource utilization of steel slag is imminent. In this paper, alkali-activated ultra-high-performance concrete (AAM-UHPC) was prepared by replacing ground granulated blast furnace slag (GGBFS) powder with different proportions of steel slag powder, and its workability, mechanical properties, curing condition, microstructure, and pore structure were investigated. The results i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
1
0
0
Order By: Relevance
“…The active silica and alumina content in steel slag is lower than that in slag, and the addition of steel slag will theoretically reduce the compressive strength of the sample. However, this study found that the addition of suitable steel slag can improve the strength to a certain extent, and Song et al [42] and Shi et al [43] also reached the same conclusion. The presence of this phenomenon is due to the high content of insoluble materials, primarily calcium carbonate, within the steel slag.…”
Section: Discussionsupporting
confidence: 64%
“…The active silica and alumina content in steel slag is lower than that in slag, and the addition of steel slag will theoretically reduce the compressive strength of the sample. However, this study found that the addition of suitable steel slag can improve the strength to a certain extent, and Song et al [42] and Shi et al [43] also reached the same conclusion. The presence of this phenomenon is due to the high content of insoluble materials, primarily calcium carbonate, within the steel slag.…”
Section: Discussionsupporting
confidence: 64%
“…Such types of waste include waste from the fuel and energy complex and waste from gas and oil plants. For example, with regard to the use of fuel and energy complex waste in construction technology, there are many works on the use of fly ash [4][5][6][7][8][9], slag [10][11][12][13][14][15] and microsilica [16][17][18][19][20][21][22]. As for gas and oil production, the main types of waste are oil sludge, spent proppant and sulfur.…”
Section: Introductionmentioning
confidence: 99%